How Much Does Internal Dialogue Affect Students' Public Speaking Anxiety? - Tiara Gita Nurahmah Dona; Feida Noor Laila Isti'adah (Edupotensia Foundation, 2025)
This study aims to analyze the relationship between internal dialogue and public speaking anxiety among tenth-grade students at SMAN 9 Tasikmalaya. Using a descriptive quantitative approach and correlational design, the study involved 167 students selected through simple random sampling. The instruments used were the Public Speaking Anxiety Scale (PSA-S) to measure public speaking anxiety and the Internal Dialogue Activity Scale (IDAS) to assess internal dialogue. Data analysis employed the Pearson Product Moment (PPM) correlation technique. The results showed a negative correlation between constructive internal dialogue and public speaking anxiety, with a correlation coefficient of -0.353, indicating that more constructive internal dialogue is associated with lower levels of public speaking anxiety. Conversely, a positive correlation was found between destructive internal dialogue and public speaking anxiety, with a correlation coefficient of 0.437, indicating that more destructive internal dialogue is associated with higher levels of public speaking anxiety. The findings also revealed gender-based differences, with female students experiencing higher levels of public speaking anxiety compared to male students. This research contributes to understanding the role of internal dialogue in public speaking anxiety and its implications for counseling-based interventions, such as Cognitive Behavioral Therapy (CBT), to help students manage public speaking anxiety.